Policy Adjustment to Exploit Opportunities in WTO, APEC and AFTA: Tradable Goods Sector - Myrna S. Austria (Philippine Institute for Development Studies (PIDS), 1999)
The fast economic integration of the world in the 1990s has brought new players, new products and new technology into the market, paving the way for intense market competition. In response to this development, the Philippines embarked on a clear-cut change in trade policy in the 1990s, via participating into WTO, AFTA and APEC. Recent development includes the objective to fast-track certain liberalization efforts including the Early Voluntary Sectoral Liberalization initiative under APEC and the Information Technology Agreement under WTO. This paper's objective is to analyze the application of these recent trade policy developments and to present a forward-looking approach on how best the business sector and the government can respond and adapt to these changes in the face of the ongoing regional crisis.
Keywords: 330; regulation and control; trade sector; information technology (IT); trade policies; tradeable goods